2018
DOI: 10.1177/0267658318787231
|View full text |Cite
|
Sign up to set email alerts
|

Input effects across domains: The case of Greek subjects in child heritage language

Abstract: A recurring question in the literature of heritage language acquisition, and more generally of bilingual acquisition, is whether all linguistic domains are sensitive to input reduction and to cross-linguistic influence and to what extent. According to the Interface Hypothesis, morphosyntactic phenomena regulated by discourse–pragmatic conditions are more likely to lead to non-native outcomes than strictly syntactic aspects of the language (Sorace, 2011). To test this hypothesis, we examined subject realization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 67 publications
(162 reference statements)
7
63
1
Order By: Relevance
“…Importantly, when chronological age was added into the model along with the other background variables, it was no longer significant, and HL use explained more variance in the data. This finding is line with other recent studies with HL children that found that HL use can override chronological age effects in heritage contexts (Daskalaki et al, 2018;Gagarina & Klassert, 2018). Given that in a HL context, the degree of HL use does not necessarily increase with age, HL use was a more reliable predictor than age.…”
Section: Individual Differencessupporting
confidence: 92%
“…Importantly, when chronological age was added into the model along with the other background variables, it was no longer significant, and HL use explained more variance in the data. This finding is line with other recent studies with HL children that found that HL use can override chronological age effects in heritage contexts (Daskalaki et al, 2018;Gagarina & Klassert, 2018). Given that in a HL context, the degree of HL use does not necessarily increase with age, HL use was a more reliable predictor than age.…”
Section: Individual Differencessupporting
confidence: 92%
“…For an overview of the role of input in minority contexts, see Unsworth, 2018) Predictions With respect to the first two questions, we predicted that the bilingual heritage groups would produce more preverbal subjects than the monolingual groups. This is in line with existing studies showing that bilingual populations speaking a free and a rigid SVO word order language combination tend to extend the use of preverbal subjects in ungrammatical or pragmatically nonfelicitous contexts (for Greek-English bilinguals, see Sorace, 2007 andDaskalaki et al, 2018; for Spanish-English bilinguals, see Cuza 2012Cuza , 2016. Furthermore, we predicted an effect of generation for both children and parents, in view of the studies suggesting that accuracy decreases with generation (Montrul, Bhatt, and Girju, 2015;Montrul and Sánchez-Walker, 2013;Pascual y Cabo, 2018;Silva-Corvalán, 1991).…”
Section: Research Questionssupporting
confidence: 90%
“…More recently, Daskalaki et al (2018) replicated Argyri and Sorace's (2007) production task with a different population: bilingual children learning Greek as a heritage language in North America (Western Canada and New York City). Whereas Argyri and Sorace (2007) examined the role of input through a between-groups comparison, Daskalaki et al studied the role of language use (measured as the mean proportion of Greek received and produced by the children in the home environment) as a continuous variable.…”
Section: Acquisition Studiesmentioning
confidence: 99%
See 2 more Smart Citations